2013
DOI: 10.1111/ijmr.12011
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of International Opportunity in International Entrepreneurship: A Review and a Research Agenda

Abstract: Recent research in the field of international entrepreneurship (IE) has emphasized the concept of international opportunity. The entrepreneurial behaviors focused on international opportunities have been found to be critical in IE. International opportunities, however, are often depicted in rather abstract and unspecified ways, and the research suffers from narrow theoretical discussion in relation to the concept of opportunity. To address these issues, the authors draw from entrepreneurship research and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
217
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(229 citation statements)
references
References 178 publications
(442 reference statements)
4
217
0
8
Order By: Relevance
“…In building on this conceptualization, we recognize that multiple definitions of ''opportunity'' exist (e.g., Mainela, Puhakka, & Servais, 2014). Definitions in entrepreneurship tend to conceptualize opportunities as situations where it is possible to introduce something new to a market (Alvarez, Barney, & Anderson, 2013;Shane & Venkataraman, 2000), while definitions in international business tend to conceptualize opportunities as situations where it is possible to enter new foreign markets (e.g., Ellis, 2011;Johanson & Vahlne, 2009;Santangelo & Meyer, 2011).…”
Section: Categories In International Entrepreneurship Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In building on this conceptualization, we recognize that multiple definitions of ''opportunity'' exist (e.g., Mainela, Puhakka, & Servais, 2014). Definitions in entrepreneurship tend to conceptualize opportunities as situations where it is possible to introduce something new to a market (Alvarez, Barney, & Anderson, 2013;Shane & Venkataraman, 2000), while definitions in international business tend to conceptualize opportunities as situations where it is possible to enter new foreign markets (e.g., Ellis, 2011;Johanson & Vahlne, 2009;Santangelo & Meyer, 2011).…”
Section: Categories In International Entrepreneurship Researchmentioning
confidence: 99%
“…Process research tends to examine temporal sequences of events (Langley, 1999) and recent entrepreneurship research has shown how it can be used to understand better the nature of entrepreneurial opportunity (for example, McMullen & Dimov, 2013;Suddaby, Bruton, & Si, 2015). However, despite the apparent match between process theory and the dynamics of entrepreneurial internationalization, reviews of opportunity-based research in international entrepreneurship (Mainela et al, 2014) and process-based research in international business (Welch & Paavilainen-Mäntymäki, 2014) have few empirical studies in common.…”
Section: Direction 2: Highlighting Dynamicsmentioning
confidence: 99%
“…Such a change of speed is likely to be driven by the firm recognizing and beginning to exploit opportunities (Mainela et al 2014). Opportunities related to the different commitment activities are new and valuable customers, suppliers, products, technologies, etc., which are perceived to have a positive influence on growth.…”
Section: From Deceleration To Acceleration: Exploiting Opportunitiesmentioning
confidence: 99%
“…IE does not only cover topics related to internal aspects of the firm but also how entrepreneurs interact with external factors, such as the dynamics of international markets. In this sphere of analysis, the study of networks has provided the backdrop to analyse opportunity recognition (Ardichvili, Cardozo, & Ray, 2003;Mainela, Puhakka, & Servais, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding opportunity -as a vital factor within entrepreneurial activities − the conceptual discussion in the literature has turned into the debate as to whether entrepreneurs identify or recognise opportunities (Alvarez et al, 2013;Andersson & Evers, 2015;Ardichvili et al, 2003;Chandra et al, 2009;Chandra et al, 2015;Eckhardt & Shane, 2003;Heilbrunn, 2010;Mainela et al, 2014;Mary George et al, 2016;Oyson & Whittaker, 2015;Shane, 2000;Vaghely & Julien, 2010). This peculiar debate is quite important due to the need to capture the process itself.…”
Section: Unbundling the Entrepreneurial Opportunity Identification Prmentioning
confidence: 99%